2017
DOI: 10.1590/0100-3984.2016.0093
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution computed tomography findings in eight patients with hantavirus pulmonary syndrome

Abstract: Objective:The purpose of this study was to describe the high-resolution computed tomography (HRCT) findings in patients with hantavirus pulmonary syndrome (HPS).Materials and Methods: We retrospectively reviewed HRCT findings from eight cases of HPS. All patients were men, aged 19-70 (mean, 41.7) years. Diagnoses were established by serological test (enzyme-linked immunosorbent assay) in all patients. Two chest radiologists analyzed the images and reached decisions by consensus.Results:The predominant HRCT fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…Hantavirus infection, caused by RNA virus of Bunyaviridae family, is characterized by flu like symptoms in the first 3 days that rapidly progress to respiratory distress, with dyspnea, lung infiltrates, pleural effusion and peribronchovascular/smooth septal thickening that are typical in ALI/ARDS of different causes (Pinto et al, 2014 ; de Lacerde Barbosa et al, 2017 ).…”
Section: Acute Lung Injury/acute Respiratory Distress Syndrome (Ali/amentioning
confidence: 99%
“…Hantavirus infection, caused by RNA virus of Bunyaviridae family, is characterized by flu like symptoms in the first 3 days that rapidly progress to respiratory distress, with dyspnea, lung infiltrates, pleural effusion and peribronchovascular/smooth septal thickening that are typical in ALI/ARDS of different causes (Pinto et al, 2014 ; de Lacerde Barbosa et al, 2017 ).…”
Section: Acute Lung Injury/acute Respiratory Distress Syndrome (Ali/amentioning
confidence: 99%
“…English proficiency is crucial for the professional growth of physicians, since it allows adequate access to updated medical information ( 4 , 5 ) , as well as participation in international conferences and meetings. In this context, the main radiology journal in Brazil accepts and had published articles in English ( 6 - 12 ) . Given the lack of studies on bilingual education in radiology, especially musculoskeletal imaging, we were motivated to analyze the integration method of English into radiology instruction.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the Barbosa et al ( 4 ) study contributes important information on the patterns of HRCT findings in a series of patients with HPS. Knowledge of the main radiological and tomographic patterns of HPS, taken together with the relevant clinical and epidemiological data, provides a fundamental contribution to the differential diagnosis of HPS, as well as to the management of HPS patients with acute febrile illness and severe respiratory distress syndrome.…”
mentioning
confidence: 82%
“…There have been only a few case reports describing the tomographic findings of HPS ( 1 - 3 ) , and there have been none presenting HRCT findings in a series of patients. In the previous issue of Radiologia Brasileira , Barbosa et al ( 4 ) published an important study on the HRCT findings in eight patients with confirmed HPS.…”
mentioning
confidence: 99%